Síntese e caracterizações de nanopartículas de FeCo/(Fe,Co)3O4 com acoplamentos magnéticos sintetizadas pelo método sol-gel proteico - Dias, Diego Felix (2015)
FeCo Nanoparticles coated with (Fe,Co)3O4 (Magnetite doped with cobalt) were synthesized by the chemical route known as Sol-Gel Protein. The synthesized materials were characterized by thermogravimetry (TG), X-Ray Diffraction (XRD), Vibrating Sample Magnetometry (VSM), Mössbauer spectroscopy, Scanning Electronic Miscroscopy (SEM) and Transmission Electronic Microscopy (TEM). The results show that the increase in temperature directly influences the size of the shell (Shell) and increased the ratio of remanent magnetization to the saturation magnetization. The effect of Exchange Spring and Exchange Bias were observed in the hysteresis curves. The Core-Shell structure was formed a non-homogeneous manner, ie not all the magnetite particles were coated.